Adsorption Studies of Synthetic Batik Dye Using Granular Activated Carbon in Continuous System - Mohamad Norahiman, Abdurahman (2012)
From this experiment, activated carbon as the adsorbent which from coconut shell is taken from industry. As well as methylene blue as the adsorbate. Dye will be flowed to the packed bed continuously. Two parameters will be concerned in this experiment which is initial concentration and time. In order to determine how this parameters will affect the adsorption process, so the percentage of loss concentration of dye will be determined. What will be expected is the higher initial concentration, the higher the adsorption capacity. Similar to time parameter, the longer time it takes, the percentage of concentration loss will be increase. So, from the data,the maximum percent removal of methylene blue is 87.7% for 40 ppm MB concentration, and adsorption start to constant after 3 hour contact time